The River : A Novel - Lewis, Beverly 1949- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2014)
"When two sisters return home for a visit after leaving the Amish world, both are troubled by the secrets--and the people--they left behind"--
Keywords: Amish -- Fiction; Sisters -- Fiction; Lancaster County (Pa.) -- Fiction; Christian fiction